2008
DOI: 10.1128/ec.00064-08
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Actin-Related Protein Is Associated with Daughter Cell Formation in Toxoplasma gondii

Abstract: Cell division in Toxoplasma gondii occurs by an unusual budding mechanism termed endodyogeny, during which twin daughters are formed within the body of the mother cell. Cytokinesis begins with the coordinated assembly of the inner membrane complex (IMC), which surrounds the growing daughter cells. The IMC is compiled of both flattened membrane cisternae and subpellicular filaments composed of articulin-like proteins attached to underlying singlet microtubules. While proteins that comprise the elongating IMC ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…In addition to Rab11B, the actin-like protein 1 (ALP1) may assist in the development of the IMC membranes. It has been shown that ALP1 appears at the bud before other members of the IMC family, such as IMC1, suggestive of a role in early daughter formation (Gordon et al , 2008). The end of bud initiation is marked by the appearance of MORN1 on the daughter buds.…”
Section: Coordinated Development and Dynamics Of The Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Rab11B, the actin-like protein 1 (ALP1) may assist in the development of the IMC membranes. It has been shown that ALP1 appears at the bud before other members of the IMC family, such as IMC1, suggestive of a role in early daughter formation (Gordon et al , 2008). The end of bud initiation is marked by the appearance of MORN1 on the daughter buds.…”
Section: Coordinated Development and Dynamics Of The Cytoskeletonmentioning
confidence: 99%
“…The myosin family has several additional members whose roles in cytoskeletal development and cell division have yet to be evaluated (Foth et al, 2006; Heintzelman, Schwartzman, 2001; Polonais et al , 2011a; Santos et al , 2009). In addition, a role for IMC assembly was suggested for ALP1 (Gordon et al, 2008), which is also a member of an extensive family (Gordon, Sibley, 2005). Although the function of these myosins and actin-like proteins has not been determined, it is likely that some of these function in cell division.…”
Section: Mechanistic Insights From Disruption Of Cytoskeletal Compmentioning
confidence: 99%
“…These proteins share between 17 and 60% amino acid identity with conventional actins. Seven of these ARPs, termed actin-like proteins (ALPs), are novel to apicomplexans (18), and T. gondii ALP1 (TgALP1) was implicated in the formation of daughter cell membranes during parasite division (17). Overexpression of TgALP1 interrupted the formation of the daughter cell inner membrane complex (IMC), leading to delayed intracellular growth (17).…”
mentioning
confidence: 99%
“…Seven of these ARPs, termed actin-like proteins (ALPs), are novel to apicomplexans (18), and T. gondii ALP1 (TgALP1) was implicated in the formation of daughter cell membranes during parasite division (17). Overexpression of TgALP1 interrupted the formation of the daughter cell inner membrane complex (IMC), leading to delayed intracellular growth (17). Very recently, a new actin-related protein (ARP4) was assigned as a key nuclear protein involved in chromosome segregation in T. gondii (45).…”
mentioning
confidence: 99%
“…Nuclear ARPs have been identified in many organisms, including plants, 10 insects 11 and protists. 12,13 However, here we will deal mainly with ARPs from budding yeast and vertebrates.…”
Section: From Discovery To Novel Roles In Nuclear Organizationmentioning
confidence: 99%